PERAN PROFITABILITAS DALAM MEMEDIASI KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Riyanto, Sugeng; Widyakto, Adhi; Fresiliasari, Oktavie; Cahyani, Anna (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
Business competition in Indonesia is increasing from year to year, with the increasing number of companies. This will affect competitive and tight competition, competition between investors or consumers. With an increase in investors, it can increase the value of the company seen from the level of debt, profit level, and company size. Thus, it can generate competitive profits for the company. This study aims to examine the effect of Price to Book Value, Leverage and Dividend Policy on Firm Value with Profitability as an intervening variable. Profitability as an intervening variable listed on the Indonesia Stock Exchange for the period 2018-2022. Indonesia Stock Exchange for the period 2018-2022. This research was conducted by means of purposive sampling with certain criteria. So that the data used as many as 72 Infrastructure companies as a research method. Sample The sample used was 5 periods, so the final sample in this study was 60observations and using data analysis using the SmartPLS application tool SmartPLS application. The results of this study prove that the Debt Equit Ratio has no effect on Price Book Value. effect on Price Book Value, Debt Equit Ratio has a significant positive effect on Return on Equity significant positive effect on Return on Equity, Dividend Payout Ratio has no effect on Price Book Value has no effect on Price Book Value, Dividend Payout Ratio has a significant positive effect on Return on Equity. significant positive effect on Return on Equity, Return on Equity has a significant positive effect on Price Book Value, and the Debt Equity Ratio variable has a significant positive effect on Return on Equity variable has a significant positive effect on Return on Equity and Price Book Value as intervening Book Value as intervening. While the Dividend Payout Ratio has significant positive effect on Return On Equity and Price Book Value as intervening as intervening